Student college for aspiring teacher trainees - Varga, Aranka (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The initiative of the student college that will be presented in this paper builds on the objectives and the traditions of the student college system in a way that it applies a special form of organization, the system of co-operation in order to involve the teacher trainees. The investigation of the structure, commencement and primary activities of the student college aims at presenting a new scientifi c-professional community and outlining the practical benefits of implementing the theory and practice of co-operation in an important segment of higher education.